Emotional intelligence and education-related stress among baccalaureate nursing students in Indonesia: A cross-sectional study - Tarigan, Mula; Silitonga, Hanna Yudit Lamro; Purba, Jenny Marlindawani; Nurhidayah, Rika Endah; Nilvarangkul, Kessarawan (Belitung Nursing Journal, 2025)
Background: Nursing students frequently encounter education-related stress (ES) arising from demanding academic workloads, clinical responsibilities, and personal adjustments during their training. Persistent stress can negatively impact learning outcomes, clinical performance, and psychological well-being. Emotional intelligence (EI), which involves the ability to perceive, understand, and manage emotions in oneself and others, is recognized as a protective factor that helps individuals regulate stress and adapt to challenges. However, research exploring the relationship between EI and ES among nursing students in Indonesia remains limited. Objective: This study examined the association between EI and ES among baccalaureate nursing students at a public university in Indonesia. Methods: A cross-sectional correlational design was conducted from September to November 2024 with 225 participants selected through stratified random sampling. Data were collected using the Indonesian version of the Trait Emotional Intelligence Questionnaire–Short Form and the Indonesian-translated Arabic Higher Education Stress Inventory. Descriptive statistics summarized the levels of EI and ES, while Spearman’s correlation, Mann–Whitney U, and Kruskal–Wallis tests were used to assess associations between variables. Results: Most students demonstrated moderate levels of EI (73.8%) and ES (64%). The median (IQR) scores were 138.00 (29) for EI and 37.00 (8) for ES. A significant negative correlation was found between EI and ES (rₛ = -0.445, p <0.01), indicating that students with higher EI experienced lower stress levels. Among demographic variables, only gender was significantly associated with ES (p = 0.05), with men reporting higher mean ranks than women. Conclusion: The findings highlight the importance of emotional intelligence in mitigating education-related stress among nursing students. Incorporating EI development into nursing curricula through emotional regulation training, reflective practices, and social–emotional learning strategies can build resilience, improve coping skills, and boost students’ academic and clinical performance. Further long-term studies are recommended to investigate the causal relationships and effectiveness of EI-based interventions.